Overexpression of pdeR promotes biofilm formation of Paracoccus denitrificans by promoting ATP production and iron acquisition - Wang, Na; Gao, Jie; Xiao, Shujie; Zhuang, Guoqiang (Frontiers in Microbiology, 2022)
Bacterial biofilms are ubiquitous in natural environments and play an essential role in bacteria’s environmental adaptability. Quorum sensing (QS), as the main signaling mechanism bacteria used for cell-to-cell communication, plays a key role in bacterial biofilm formation. However, little is known about the role of QS circuit in the N-transformation type strain, Paracoccus denitrificans, especially for the regulatory protein PdeR. In this study, we found the overexpression of pdeR promoted bacterial aggregation and biofilm formation. Through RNA-seq analysis, we demonstrated that PdeR is a global regulator which could regulate 656 genes expression, involved in multiple metabolic pathways. Combined with transcriptome as well as biochemical experiments, we found the overexpressed pdeR mainly promoted the intracellular degradation of amino acids and fatty acids, as well as siderophore biosynthesis and transportation, thus providing cells enough energy and iron for biofilm development. These results revealed the underlying mechanism for PdeR in biofilm formation of P. denitrificans, adding to our understanding of QS regulation in biofilm development.